WATER FILTRATION DEVICE IMPROVING AND REDESIGN - Abu Shaqdam, Qais; Breik, Omar (My University, 2021)
One of the most important devices in the world are those related to water filtration. The biggest advantage of the device we are trying to design is its ability to filter seawater and make it usable for several human needs, including drinking. These devices are already existed but in large size and huge cost. It is also not available in many countries which suffers from crises, disasters and also in the developing countries. The aim of this project is to improve and fix a filtration device that is already existed in the scientific research centers at An-Najah National University. The filtration device has many faults and hasn’t been working properly for more than a year. We have been working and testing the electrical parts in the device, we were able to fix many electrical issues that hasn’t been considered in the design stage. Other problems were related to software and coding, we had to go over all the software parts and modify it to serve the purpose it was designed for. Understanding the device work was challenging. A mechanical, chemical and electrical systems works in an integrated way, we had gone through all these systems and break them down in order to fix and improve the device.